Rapid Weight Changes and Competitive Outcomes in Muay Thai and Mixed Martial Arts: A 14-Month Study of 24 Combat Sports Events - Colin S. Doherty; Lauren V. Fortington; Oliver R. Barley (MDPI AG, 2024)
This study investigates the rapid weight loss (RWL) and rapid weight gain (RWG) of contest winners and losers from Muay Thai (MT) and mixed martial arts (MMA) events. The relationship between rapid weight change variables of males and females, and competitive success is also examined. Data from a weight management questionnaire was collected one day post-competition from 185 participants across 24 fight events, resulting in 263 responses (MMA: n = 78, MT: n = 185). Official and secondary weigh-in data were provided by the Combat Sports Commission. The results show that in MT, contest winners compared to losers had significantly greater RWL-7 days (5.9 ± 2.6% vs. 4.6 ± 2.7%, p = 0.01), RWG (6.2 ± 2.9% vs. 4.7 ± 2.8%, p = 0.003), and RWG/RWL ratio (108% [86-132%] vs. 86% [60-119%], p = 0.038), while no significant differences were observed for MMA. Mixed logistic regression models that controlled for age showed that a 1% increase in female RWL-24 h ([OR = 1.57, R2 = 0.105, p = 0.001]) was associated with a 1.6 times higher likelihood of winning compared to female athletes without this increase. We emphasise that associations do not imply causation, and it is possible that other factors which align with rapid weight change practices may impact the observed relationship. Nonetheless, MT contest winners show greater RWL, RWG, and RWG/RWL ratio than losers, and female rapid weight changes appear to be associated with competitive success in this cohort.